1994
DOI: 10.1105/tpc.6.10.1401
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phenotypes generated by overexpression and suppression of S-adenosyl-L-methionine synthetase reveal developmental patterns of gene silencing in tobacco.

Abstract: S-Adenosyl-L-methionine synthetase (SAM-S) catalyzes the conversion of L-methionine and ATP into S-adenosyl-L-methionine. Tobacco plants that were transformed with a construct allowing high transcription levels of an Arabidopsis sam-s gene could be grouped into two main classes based on their morphology. One class developed yellow-green leaves and had high SAM-S activity and transgene mRNA levels, whereas the other class was stunted and had leatherlike leaves, very low SAM-S activity, and suppressed mRNA leve1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(48 citation statements)
references
References 36 publications
(41 reference statements)
3
45
0
Order By: Relevance
“…4). This ubiquitous presence is probably due to the metabolic importance of SAM and is in agreement with the character of 'housekeeping' gene attributed to SAMs [3,25,26]. In spite of its generalized expression, SAMs levels were found to be higher in roots than in leaves and stems (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…4). This ubiquitous presence is probably due to the metabolic importance of SAM and is in agreement with the character of 'housekeeping' gene attributed to SAMs [3,25,26]. In spite of its generalized expression, SAMs levels were found to be higher in roots than in leaves and stems (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Some authors have justified the existence of different genes by the metabolic importance of SAM [26,38]. However, it has been also suggested that a part of the SAMs genes would be expressed constitutively while other copies would be specifically regulated by developmental [3,25], hormonal [21], or environmental factors [6,16], always strictly controlled according to the need of SAM [3].…”
Section: Introductionmentioning
confidence: 99%
“…Co-suppression of host genes and transgenes expressing the same coding sequence has now been reported in the case of several plant genes: chalcone synthase [15,19], dihydroflavonol reductase [20], polygalacturonase [18], chitinase [9], phytoene synthase [8], pectinesterase [17], S-adenosyl-L-methionine synthetase [1] and nitrite reductase [22]. Similarly, suppression of reporter transgene expression occurring at each generation has also been reported [3,4,11].…”
Section: Introductionmentioning
confidence: 93%
“…AdoMet is the major methyl-group donor for numerous transmethylation reactions in both prokaryotes and eukaryotes (Tabor and Tabor 1984;Boerjan et al 1994). Plants produce a multitude of secondary products that include one or more methyl groups added during their biosynthesis by methyltransferases, many of which use AdoMet as the methyl-group donor.…”
Section: Introductionmentioning
confidence: 99%